Kajian Yuridis Batas Waktu Tinggal Pengungsi Di Negara Transit Berdasarkan Hukum Pengungsi Internasional - Pangestu, Devin Catur; Jayakusuma, Zulfikar; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Migration has a long history that concists of many motives. Migration flow phenomenon are gettingworse by political conflicts in some of the Asian and African countries. The migrant often to be called asrefugees. The migration process that has been done are not obedient according to migration acts or theillegal migration could cause threat towards sovereignity, security, social life, and economy even it couldcause threat towards a nation’s ideology. From this problems background, there are issues which are first,how is the International Refugee Law regulate the living duration standards in the transit state? Secondly,how is the application of the regulation minding the living duration standards for refugees in the transitstate? The purposeof this thesis is to acknowledge the living duration standards according to InternasionalRefugee Law and to understand the living duration standards in transit state.The research conducted can be classified as legal-normative methode. This research is specified on theapplication of non-refoulement pricipal also the law systematic towards convention and regional regulation.Concluded from this research, first, the regulation related to living duration standards for refugees inthe International law is yet not confirmed in Geneva Convention 1951. Although, regional regulation.Secondly, the application of living duration standards in the transit states are having few problems,commonly caused by the unregulated issues related to living duration standard. Refugees are considered asillegal immigrants, and that is why they were located in certain place and they could not get their way out(detention).Keywords: Refugees-Transit State-Living Duration Standards